Model predictive power control for grid-tied inverters under unbalanced and distorted grid conditions. (November 2022) - Zhang, Zhi; Kang, Longyun; Hu, Bihua
Abstract: Normally, a grid-tied inverter with model predictive power control (MPPC) possesses a fast dynamic response and outstanding static performance. However, under unbalanced and distorted grid conditions, such a grid-tied inverter is troubled by considerable unwanted grid-current distortion. Here, a modifying power reference MPPC (MPR-MPPC) is proposed to address the above issue. Considering the characteristics of the output power, the revised power references are derived to mitigate the grid-current distortion and achieve three alternative targets (minimization of active- and reactive-power oscillation and balancing of the grid currents). However, these corresponding power references only consider one of three targets, and the oscillation amplitudes of active and reactive power are inversely proportional. Then, the three-target power references are incorporated into a single reference with two parameters to regulate the magnitude of active/reactive-power oscillation comprehensively. Finally, an experimental platform is established to demonstrate the validity of MPR-MPPC and the results show that the MPR-MPPC meets expectations. Highlights: A model predictive control with modifying power references. Grid-tied inverter under unbalanced and distorted grid condition. Suppress grid-current distortion and achieve one of the three targets. Comprehensively regulate power oscillation magnitudes.